Iliana Sarafian: Contesting moralities: Roma identities, state and kinship: New York: Berghahn Books, 2023, 144 s., ISBN: 978-1-80073-906-2, ISBNebook: 978-1-80073-907-9 - Viková, Lada (Romano džaniben, 2023)
RECENZE